A novel method for evaluating the slurry coating characteristics of sized yarns based on the starch-iodine color reaction principle and image processing. Issue 11 (June 2021) - Yan, Wenjun; Zhu, Bo; Liu, Jianli; Gao, Weidong
The slurry coating characteristics of sized yarns directly impact warp weavability. Due to the damage to sized films, the conventional methods of detecting sized-yarn coating characteristics have drawbacks of low efficiency and poor repeatability. A novel detecting method of slurry coating characteristics was proposed based on image processing. Through the starch-iodine color reaction principle, a self-made dynamic image acquisition device was developed in this paper, in which the apparent images of starch-based sized yarns after color reaction were captured consecutively. The slurry coating percentage ( SCP ), slurry coating depth ( SCD ) and slurry coating unevenness ( SCU ), respectively reflecting the sizing coating integrity, sizing coating thickness and thickness unevenness, were extracted by image processing. The effects of experimental parameters, including immersion time and concentration of I2 -KI solution, on slurry coating characteristics were analyzed, and central composite design was adopted to optimize the stability of the test system. Sized yarns commonly used in textile mills were characterized by the proposed method. The experimental results indicated that immersion time of 3.56 min and I2 -KI concentration of 0.11‱ (‱ represents that the mass of the solute is one ten-thousandth of solution) led to the optimal stability of slurry coating characteristics (the CV of SCP, CV of SCD and CV of SCU were 3.32%, 5.56% and 9.37%, respectively). The much lower CV of the proposed method compared with conventional ones confirmed that the method was useful for evaluating slurry coating characteristics.